Epidemiologia, sinais clínicos e distribuição das lesões encefálicas em bovinos afetados por meningoencefalite por herpesvírus bovino-5 (BoHV-5) - Rissi, Daniel Ricardo (2007)
Seven outbreaks and an isolated case of meningoencephalitis caused by bovine herpesvirus-5 (BoHV-5) in cattle from Rio Grande do Sul, Brazil, occurring in 2002-2004 are described. From a total population at risk of 1,359 cattle, 54 1-18-month-old calves from both sexes and several breeds were affected and 50 died spontaneously or were euthanatized while moribund. The highest frequency of cases were in recently weaned calves or calves submitted to other stressing factors. General rates of morbidity, mortality and lethality were respectively 3.97%, 3.67% e 92.59%. Clinical courses varied from 3-10 days and included depression, nasal and ocular discharge, grinding of teeth, circling, blindness, fever, nistagmus, trembling, anorexia, dysphagia, drooling, incoordination, head pressing, rough hair coat, tachycardia, tachypnea, abdominal pain, melena, falls, recumbency, opisthotonus, convulsions and paddling. Nineteen calves were necropsied. Necropsy findings were characterized by hyperemia of leptomeninges, swollen of rostral portions of the telencephalon, and flattening of frontal lobes gyri; frequently in these frontal areas there were segmental brown-yellow discoloration and softening (malacia) of the cortex. In cases with more protracted clinical courses there were extensive swelling, softening and hemorrhaging of the telencephalic frontal lobes. Microscopically, all affected cattle had a necrotizing non-suppurative meningoencephalitis with variable distribution among the 19 cases and among the various telencephalic regions of the same case. The severity of these changes were more marked, in decreasing order of intensity, in the telencephalic frontal cortex, basal ganglia (nuclei), thalamus, brain stem, parietal telencephalic cortex, occipital telencephalic cortex and cerebellum. Perivascular inflammatory infiltrate consisted predominantly of lymphocytes, plasm cells, and, less frequently, neutrophils. Additional microscopic findings included variable degrees of gliosis, edema, neuronal necrosis in the telencephalic cortex characterized by shrinking and eosinophilia of perikaria and nuclear picnosis (red neuron); basophilic intranuclear inclusion bodies in astrocytes and neurons (21.05% of the cases); sattelitosis; and neuronophagia. The areas of softening in the cortical substance consisted of necrosis of the neuroctodermal elements with maintenance of mesenchymal structures (vessels and microglia), infiltrate of gitter cells, and, in more severe cases, extensive hemorrhages. In chronic cases, only vascular structures and a few gitter cells remained in the cortical area leaving a cavity between white matter and leptomeninges (residual lesion). The diagnosis was based on the epidemiological, clinical, necropsy and histopathologial findings. Viral isolation, immunofluorescent antibody technique and polymerase chain reaction were performed in three outbreaks.